Natural Pigment Screening: Comparative Analysis of Chlorophyll and Carotenoid Content and Antioxidant Potential in Various Seaweed Species - Sri Sedjati; Wilis Ari Setyati; Ali Ridlo; Intan Swastika Sari; Tiara Rahmawati (Universitas Diponegoro, 2026)
The present study aimed to evaluate the levels of chlorophyll and carotenoids, as well as the antioxidant potential of various seaweed species collected from the waters of Kartini Beach, Jepara, Central Java, Indonesia. Nine seaweed samples were extracted using methanol, and the pigment content was determined using spectrophotometric analysis. The antioxidant activity of the extracts was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The findings indicated that the green seaweed Caulerpa serrulata exhibited the highest concentrations of chlorophyll a (489.42 µg/g) and carotenoids (248.83 µg/g). Conversely, the brown seaweed Sargassum echinocarpum demonstrated superior antioxidant properties, with DPPH radical scavenging activities of 92.59%, followed by C. serrulata extracts at 76.43%. The antioxidant activity of these extracts exceeded that of ascorbic acid at a concentration of 20 µg/mL (71.21%). A moderate positive correlation was observed between pigment content and antioxidant activity. The variations in pigment composition among different seaweed species significantly influenced their antioxidant potential, with carotenoid-rich brown seaweeds exhibiting higher antioxidant activity compared to green seaweeds. The study's findings reveal the potential of C. serrulata and S. echinocarpum extracts as natural pigments with antioxidant properties. These extracts offer promising applications in the food, nutraceutical, and cosmetic industries as safe and sustainable alternatives to synthetic antioxidants and colorants.